Microbes and pathogens associated with shrimps - implications and review of possible control strategies - Bhassu, Subha; Shama, Maryam; Tiruvayipati, Suma; Soo, Tze Chiew Christie; Ahmed, Niyaz; Yusoff, Khatijah (Frontiers in Marine Science, 2024)
Shrimp aquaculture has been growing rapidly over the last three decades. However, high-density aquaculture together with environmental degradation has led to increased incidence of shrimp infections. Thus, devising and implementing effective strategies to predict, diagnose and control the spread of infections of shrimps are crucial, also to ensure biosecurity and sustainability of the food industry. With the recent advancements in biotechnology, more attention has been given to develop novel promising therapeutic tools with potential to prevent disease occurrence and better manage shrimp health. Furthermore, owing to the advent of the next-generation sequencing (NGS) platforms, it has become possible to analyze the genetic basis of susceptibility or resistance of different stocks of shrimps to infections and how sustainable aquaculture could be made free of shrimp diseases.